A Systematic Literature Review of the Impact of Cognitive Stimulation Programs on Reading Skills in Children Aged between 6 and 12 Years Old - Claudia Reina-Reina; Eneko Antón; Jon Andoni Duñabeitia (MDPI AG, 2024)
The scientific evidence regarding the possibility of transferring benefits derived from cognitive training focused on working memory and inhibitory control to reading skills in children aged 6 to 12 is inconclusive. This study carries out a systematic review of recent published studies on this topic with the aim of analysing the specific role of various cognitive stimulation programs in the growth of executive functions and reading performance in children from ages 6 to 12. Here, we present the main results reported in the most recent literature, where the impact of intervention programs on working memory and inhibitory control in children with typical development are analysed. Even though the effectiveness of executive function training programs in terms of close transfer is conspicuous, there is still a lack of convergence in recently published articles, especially regarding the effects of far transfer in reading comprehension after cognitive stimulation programs are applied.